Redução de tempo em paradas programadas para manutenção preventiva em uma linha de conformação de tubos - Martins, William Rodrigo (2014)
The following dissertation aims to analyze the productive efficiency of the forming tube line, the company Magna Cosma Brazil, the line on which it was identified that there was potential for a significant gain in production. One of the management tools applied was the OEE. Following the measurement of production times, time of failure, repair time and setup time of the line, was conducted for a period of six months for tabulation and analysis of data, and after completion of the actions raised in this work was repeated the measurements for six months to ensure the effectiveness of the results. After analyzing the data, we used another tool PDCA, to create a methodology that helps to diagnose, analyze and solve the problems raised. A methodology which generated excellent results was the SMED, dealing with the concept of fast tool change separating the task into external setup, where it performs all tasks with the machine still in production, and the internal setup, tasks that require downtime. Finally was made the improvement of maintenance plans and work instructions.